ABREACTION REVISITED TREATMENT OF PTSD BY ABREACTION - Kaiser, Fawad; Dewan, Hamayon B (Journal of Pakistan Psychiatric Society, 2006)
This paper describes the successful treatment of a 38year old man with a three months history of PTSD. The distressing dreams began shortly after the October earthquake after he had witnessed his family members dying under the collapsed roof. Previous psychiatric treatment including psychotherapy had failed to bring about any improvement. Abreaction was induced by the oral administration of sodium amytal and methylphenidate. Patient was interviewed on more than one occasions while he was under the influence of these drugs. After six sessions the nightmares stopped and normal sleep was restored. Two months after his discharge from the clinic there had been no recurrence. Drug-induced abreaction is a valuable technique in particular clinical cases. By using the oral route, its complications and inconveniences can be reduced. Key words: Posttraumatic Stress Disorder, nightmares, abreaction